A dietary combination of red yeast rice, phytosterol ester and lycopene ameliorates hypercholesterolemia by regulating gut microbiota and activating hepatic FXR-LDLR/ABCG pathway in mice - Xu, Jingxian; Huang, Xin; Pei, Fei; Chen, Yuzhu; Zhang, Cunzheng; Zhao, Lingling; Zhang, Hua; Zhang, Jindong; Duan, Liping (Frontiers in Microbiology, 2025)
BackgroundExcessive nutrition intake is a well-established contributor to obesity and hypercholesterolemia, both of which pose substantial risks to cardiovascular health. Statins, which are widely prescribed for managing serum cholesterol levels, are sometimes discontinued owing to adverse reactions. In contrast, dietary components have shown promise in lowing lipid lowering potential with a relatively higher safety profile, although the underlying mechanisms remains incompletely understood.ObjectivesThis study aimed to investigate the role and underlying mechanism of a dietary combination comprising red yeast rice (RYR), phytosterol ester, and lycopene (RPL), in mitigating hypercholesterolemia.MethodsHigh-fat, high-cholesterol (HFHC)-fed C57BL/6J mice were administered either the RPL combination (low and high dose) or simvastatin. The effects of these interventions on obesity, serum cholesterol, and glucose tolerance were evaluated. Mechanistic insights were gained through fecal 16S rRNA sequencing, targeted metabolomic profiling, and molecular analysis of liver and intestinal tissues using western blotting, qPCR, and immunofluorescence techniques.ResultsCompared to the HFHC group, low and high doses of the RPL combination reduced serum low-density lipoprotein cholesterol (LDL-C) levels by 33 and 20%, respectively, whereas simvastatin achieved a 22% reduction. Both doses of RPL significantly lowered serum total cholesterol (TC) levels and alleviated obesity in mice, effects not observed with simvastatin. Mechanistically, the RPL combination reshaped the gut microbiota, specifically increasing the abundance of Bifidobacterium and decreasing that of Clostridium, Ruminococcus and Eubacterium. Additionally, the RPL combination modulated bile acids profiles, leading to an increased proportion of hyodeoxycholic acid (HDCA) and a decreased level of omega-muricholic acid (ω-MCA). Furthermore, the altered gut microbiota and ω-MCA levels activated the hepatic FXR-LDLR/ABCG5/8 pathway, promoting cholesterol excretion into feces and thereby alleviating hypercholesterolemia. The increased proportion of HDCA suppressed lipid absorption, further facilitating its excretion in feces.ConclusionThe dietary combination of RPL effectively lowers serum cholesterol by regulating gut microbiota, influencing bile acid metabolism, and enhancing cholesterol excretion. This study offers a novel and promising strategy for the clinical management of hypercholesterolemia.